Polly of the Circus - Mayo, Margaret, 1882-1951 (Salt Lake City, UT : Project Gutenberg, 1997)
"Polly of the Circus" by Margaret Mayo is a Broadway play that opened in 1907. When a circus performer is injured and left behind in a small midwestern town, she recovers at the local minister's home. Their eleven-month time together leads to unexpected romance, but the disapproving townspeople threaten their future. Known for its dramatic love story and spectacular staging that recreated an actual circus complete with animals, the play became a Broadway success and later inspired two film adaptations. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Polly_of_the_Circus_(1907_play)
Release date is 1997-03-01
Produced by Charles Keller, and David Widger
Keywords: Circus -- Fiction; Circus performers -- Fiction